A direct solvent-free conversion approach to prepare mixed-metal metal–organic frameworks from doped metal oxides. Issue 29 (12th March 2021) - Yi, Beili; Zhao, Haojie; Zhang, Yue; Si, Xiaomeng; Zhang, Guanqun; An, Yuanyuan; Su, Longxing; Tsung, Chia-Kuang; Chou, Lien-Yang; Xie, Jin
Abstract : We propose a novel solvent-free conversion strategy of Pt–ZnO to Pt-ZIF-8. This synthesis strategy may facilitate the discovery of MMOFs that have not been reported previously. Abstract : We propose a novel strategy to introduce platinum into the metal nodes of ZIF-8 by preloading Pt as a dopant in ZnO (Pt– ZnO) and then convert it to Pt doped ZIF-8 (Pt-ZIF-8) through a chemical vapor deposition (CVD) approach. The solvent-free conversion of Pt–ZnO to Pt-ZIF-8 allows the Pt dopant in ZnO to coordinate with organic linkers directly without the formation of Pt nanoparticles, which is a general issue of many methods. This general synthesis strategy may facilitate the discovery of MMOFs that have not been reported previously.